2001
DOI: 10.1080/09500690110038558
|View full text |Cite
|
Sign up to set email alerts
|

The how's and why's of biological change: How learners neglect physical mechanisms in their search for meaning

Abstract: This study describes the trends in students' explanations of biological change in organisms. A total of 96 student volunteers (8 students from each of 2 nd , 5 th , 8 th , and 12 th grades from 3 localities) were interviewed individually and each student was presented a series of graphics depicting natural phenomena. Students' explanations to questions of how something occurred were assigned to one of three categories (responses addressing how something occurred, why something occurred, and 'I don't know'). Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 20 publications
0
78
0
1
Order By: Relevance
“…A bike, for instance, can be described mechanistically by describing the parts and their role in the whole (see Grotzer 2003 for a review on young children's appreciation of mechanisms). However, the study of Abrams and Southerland (2001) suggests that mechanistic reasoning in biology education, and especially in molecular biology education, is not as abundantly present as Russ et al (2008) report. These findings do not necessarily contradict.…”
Section: Reinterpretation Of Students' Learning Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…A bike, for instance, can be described mechanistically by describing the parts and their role in the whole (see Grotzer 2003 for a review on young children's appreciation of mechanisms). However, the study of Abrams and Southerland (2001) suggests that mechanistic reasoning in biology education, and especially in molecular biology education, is not as abundantly present as Russ et al (2008) report. These findings do not necessarily contradict.…”
Section: Reinterpretation Of Students' Learning Problemsmentioning
confidence: 99%
“…Apparently, the need to explore the causal explanations that answer 'how a cell works' is not self-evident in the biology classroom. Abrams and Southerland (2001) suggest that one of the reasons for this is the tendency of biology teachers to focus on the benefits of a phenomenon rather than on the cause, and Kampourakis et al (2011) emphasizes that teachers should be aware of the difference between proximate and ultimate causes to distinguish effectively between 'how?' and 'why?'…”
Section: Mechanistic Explanations: 'How Does It Work?' Is Not An Obvimentioning
confidence: 99%
See 1 more Smart Citation
“…Tentativeness refers to students' doubts about the plausibility of their explanations and shifting explanations mean that students give different explanations for the same phenomenon when they are questioned about it different times. In an accompanying study, Abrams et al (2001) investigated students' explanations of biological change in organisms. They found that students are unfamiliar with and unprepared for causal explanations in biology.…”
mentioning
confidence: 99%
“…Students often don't distinguish proximate from evolutionary explanations, or don't recognise what kind of time perspective their answer is supposed to deal with. Abrams, Southerland and Cummins (2001) developed the idea that there are both proximate and ultimate answers to "how and why" questions. Ariew (2003) suggests that answers to questions about "how" should refer to proximate causes; while towards "why-questions" evolutionary explanations are more fruitful.…”
Section: Explaining Biological Changementioning
confidence: 99%